2014
DOI: 10.1186/1472-6882-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification and inhibitory effect on LDL oxidation of the traditional Korean medicine, Leejung-tang

Abstract: BackgroundLeejung-tang (LJT) is a traditional Korean herbal medicine for the treatment of gastrointestinal disorders. In this study, we performed quantification analysis of five marker components, liquiritin (1), ginsenoside Rg1 (2), ginsenoside Rb1 (3), glycyrrhizin (4), and 6-gingerol (5) in LJT using a high performance liquid chromatography-photodiode array (HPLC–PDA). In addition, we investigated the inhibitory effect on low-density lipoprotein (LDL) oxidation by the LJT sample.MethodsCompounds 1–5 were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…LPCs, major lipid constituents of oxidized LDL, are generated via hydrolysis of the lipid components of oxidized LDL by lipoprotein-associated phospholipase A2. , The levels of LPCs, including LPC 20:4 and LPC 22:6, increased on ingestion of an HFD but were significantly reduced in mouse serum if the diet contained compound K. Especially, the LPC 22:6 level did not differ significantly from normal controls under such circumstances (Figure ). Earlier studies found that LDL oxidation was inhibited by ginsenosides Rb1 and Rg1 . Therefore, our work highlights the fact that the reduced LPC 20:4 and LPC 22:6 levels in the HFD+CK group may be attributable to an effect of compound K, a metabolite of ginsenoside Rb1.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…LPCs, major lipid constituents of oxidized LDL, are generated via hydrolysis of the lipid components of oxidized LDL by lipoprotein-associated phospholipase A2. , The levels of LPCs, including LPC 20:4 and LPC 22:6, increased on ingestion of an HFD but were significantly reduced in mouse serum if the diet contained compound K. Especially, the LPC 22:6 level did not differ significantly from normal controls under such circumstances (Figure ). Earlier studies found that LDL oxidation was inhibited by ginsenosides Rb1 and Rg1 . Therefore, our work highlights the fact that the reduced LPC 20:4 and LPC 22:6 levels in the HFD+CK group may be attributable to an effect of compound K, a metabolite of ginsenoside Rb1.…”
Section: Resultssupporting
confidence: 65%
“…Earlier studies found that LDL oxidation was inhibited by ginsenosides Rb1 and Rg1. 57 Therefore, our work highlights the fact that the reduced LPC 20:4 and LPC 22:6 levels in the HFD+CK group may be attributable to an effect of compound K, a metabolite of ginsenoside Rb1.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 64%
“…After this period, the medium was removed, and the antioxidant activity was evaluated using the thiobarbituric acid reactive substances (TBARS) assay. 19 The cells were seeded on a 24-well plate with a 500 μL serum-free RPMI 1640 culture medium and were treated with LDL (200 µg/mL) and samples. TBARS were evaluated exactly as previously described referring to a Malone di-aldehyde standard.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%